ANÁLISIS DE LA RED DE COMUNICACIONES DE LAS FARMACIAS CRUZ AZUL DE LA CIUDAD DE BABAHOYO - CASTRO HERNANDEZ, MATIN ALBERTO (2018)
The present case study entitled "Analysis of the communications network of the Cruz Azul pharmacies of the city of Babahoyo" is intended to determine the problems that exist in the communication of data between the Cruz Azul pharmacies of this city, which brings consequential deficiency in the attention to the public in the sixteen franchised pharmacies that exist in this city, The Cruz Azul Pharmacies are part of the Difare Group, currently has 353 franchisees, who run 814 pharmacies throughout Ecuador, and this figure continues to rise every month. The Difare Group offers franchisees training, technology, variety and inventory of products, so that they can offer a quality service to the public. The computer system that is used by franchised pharmacies is called NEPTUNO, which is special for administering pharmacies. Its purpose is to maintain a constant control of the inventories of Farmacias Cruz Azul, this system allows remote communication between autonomous teams through a network of communication, this is the means by which data is transmitted, using the internet as the Transit Network, but when the network goes down, the system is no longer efficient, the Communications Network being the axis for software operation, for this reason, the object of the present case study. It was already indicated that the program that is used is the NEPTUNO, which contains a series of modern commercial intelligence tools, this system allows the pharmacy to administer inventories, analyze sales statistics, order electronically, receive electronic invoices, optimizing the processes through this state-of-the-art technology, which also allows working in real time with communication networks of providers such as mobile telephony, banking, credit cards.